State and Economic Reform in Iraq Dialectical Intervention and Neutrality - سلطان جاسم سلطان; حسين علي عبد; علي عايد ناصر (مجلة الغري للعلوم الاقتصادية والادارية)
Iraq economy had witnessed many changes and transitions which effected upon its economic performance. After 2003, the Iraqi economy entered into new stage represented by shifting from closed to a free market. However, during fifteen years this experience did not succeed, and the economy yet suffers structural imbalance and unclear role of state in the economic activities. That led to failed state which was not able to face challenges imposed by development based on the oil industry. Concurrently, the oil rental had negative effect on implementation of economic policies which aimed to achieve welfare economy. Finally, the resource seems to create strategical interest by economic reform through exit from resource cursing and create solution of problems.